SINTESIS DAN KARAKTERISASI KARBOKSIMETIL SELULOSA (CMC) DARI LIMBAH TANDAN KOSONG KELAPA SAWIT (TKKS) SEBAGAI PENGGANTI CMC INDUSTRI - Trisnawita, Yuni; Putri, Elisa (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2024)
Empty palm bunches are industrial solid waste from the manufacture of Crude Palm Oil (CPO). Currently, the number of empty palm bunches is abundant without management, so it is necessary to think about its utilization that is more useful and without causing environmental pollution. This underlies the selection of empty palm bunches as the manufacture of CMC, so as to obtain a more useful result. This study was conducted to determine how to provide Carboxymethyl Cellulose (CMC) and to determine the characteristics of Carboxymethyl Cellulose (CMC) of palm empty bunches produced. the research method of providing CMC is carried out through the process of isolation of α cellulose, delicification, swiling, bleaching, hydrolysis and the process of alkalization and carboxymethylization to produce CMC. CMC is reviewed through the parameters of Degree of Substitution, pH and purity to produce CMC that meets the requirements of SNI CMC quality 1 and SNI CMC muti II. And from the results that have been done CMC Empty Palm Bunches show results that have met the SNI standard 1. For the parameters of the Degree of Substitution 0.7990, pH 7 and purity 99.41%. And the results of FT-IR functional groups of CMC empty palm bunches get the results of O-H, C-H, C-O functional groups. .